A Soil Mechanical Model for Deformable Grounds Under the Dynamic Action of High-Mobility Tracked Vehicles - Li, Qiang; Liu, Xintian (Recent Patents on Engineering, 2023)
Background: The mechanical properties of the soil are key factors for studying the ground adhesion capability of high-speed tracked vehicles under the action of dynamic loads. Classic mechanical models of ground surface soil are insufficient to predict the mobility of high-speed tracked vehicles. Objectives: The aim was to study a soil mechanical model for deformable grounds under the dynamic action of high-mobility tracked vehicles. Methods: According to the high loading and shear rate of high-speed heavy-duty tracked vehicles, a three-dimensional soil simulation model for deformable grounds was established. Numerical calculations were performed. Results: The correctness of the simulation model was validated through the comparison of the numercal calculation results with the soil-bin test results. Conclusion: On the basis of the empirical pressure-sinkage and the Janosi shear model of ground surface soil, and coupled with factors such as the loading and shear rate, a new improved mechanical model of ground surface soil was built for the running conditions of high-speed heavy-duty tracked vehicles. The correctness of the improved model was validated through the comparison of the calculation results of the improved model with the numerical simulation results, which provides a basis for studying the driving performance of high-speed heavy-duty tracked vehicles on deformable grounds.
Keywords: soil mechanical model